Estimation of land subsidence in deltaic areas through differential SAR interferometry: the Po River Delta case study (Northeast Italy). Issue 23 (2nd December 2018) - Fiaschi, Simone; Fabris, Massimo; Floris, Mario; Achilli, Vladimiro
ABSTRACT: River deltas are very complex environments vulnerable to flooding. Most of the world's deltas are facing the immediate threat of land subsidence that jeopardizes the safety of millions of people worldwide. In Italy, the Po River Delta (PRD) (Northeast Italy) is an area historically affected by high rate of subsidence due to natural and anthropic factors. Even if the subsidence rates remarkably reduced during the last three decades, this process continues to be alarming in particular in low-lying sectors and along the coastline, where the loss of elevation, combined with the sea-level rise, increases the risk related to flooding. In this study, we monitored the subsidence affecting the entire PRD area with advanced differential interferometric synthetic aperture radar (A-DInSAR) techniques applied to three C-band SAR data sets acquired by the European Remote Sensing satellites, Environmental Satellite, and Sentinel-1A satellite in the last 25 years (from 1992 to 2017). The results of the interferometric processing, consisting of both mean velocity and displacement time series along the satellite line of sight, validated by comparison with levelling and global positioning system measurements, show increasing subsidence moving from the inland to the coastline, with maximum deformation velocities, for the most recent data, in the order of −30 mm year −1 . In particular, many embankments near the coastal area are affected by high values of subsidence, which increase the flooding hazard of the entire deltaic territory. This work shows the importance of adopting A-DInSAR techniques to update the knowledge of the extent and rates of deformation of subsiding areas in low-lying territories such as river deltas. The outputs of such monitoring can be of primary importance for the future protection of the territory and the flooding risk mitigation.